Planeación Financiera en la Farmacia Alexandra del Cantón Catamayo de la Provincia de Loja, Período 2016-2020 - Castillo Suing, Katherine Elizabeth (2016)
This thesis entitled "Financial Planning in Alexandra Pharmacy Catamayo canton of the Province of Loja, period 2016-2020", has a policy to meeting the goals set at the beginning of work, starting with the overall objective structure consisting of: make a financial planning at the Alexandra Pharmacy Canton Catamayo Loja Province, period 2016 - 2020, in order to meet their future income, make decisions that contribute to business growth and resource optimization. The methodology used to develop these goals begins with the collection of reliable information and financial statements 2015 of the company, once organized the information relevant and coherent manner, in the practical part specific objectives are developed, being the following: develop a sales forecast, in order to meet future economic performance, which would maximize the opportunities, being necessary to the development of this objective to build upon information sales and historical purchases by 2015, and by the method of increase we determine the monthly percentage increase which in turn allows to know the seasons more revenue for the company; Make a cash budget to forecast future inflows and outflows of money, and prevent unexpected future problems in this objective the cash budget which will serve to determine whether the entity has sufficient liquidity or requires financing for development is made the same programs inflows and outflows of cash 5 was considered; Prepare pro forma financial statements projected the years 2016- 2020, the Alexandra Pharmacy Catamayo canton finally the pro forma statements, the Income Statement and the Balance Sheet proforma order to meet expected costs and revenues for the following year is done and future economic position is, assets, liabilities and equity at the end of the period. It is noteworthy that the percentage of sales method was used for processing. Once completed the entire process and the final results obtained it was concluded that the Pharmacy Alexandra will not have a cash deficit so you can cover its short-term obligations. In the final part of this research work conclusions and recommendations are presented.